Reactive oxygen species turnover, phenolics metabolism, and some key gene expressions modulate postharvest physiological deterioration in cassava tubers - Wahengbam, Elizabeth Devi; Devi, Chingakham Premabati; Sharma, Susheel Kumar; Roy, Subhra Saikat; Maibam, Albert; Dasgupta, Madhumita; Luikham, Star; Chongtham, Tania; Ningombam, Arati; Bhupenchandra, Ingudam; Singh, Laishram Kanta; Devi, Yumnam Prabhabati; et al. (Frontiers in Microbiology, 2023)
Rapid postharvest physiological deterioration (PPD) in cassava (Manihot esculenta Crantz) tuber is a significant concern during storage. The freshly harvested tubers start spoiling within 24 to 72 h. Accumulation of H2O2 is one of the earliest biochemical events that occurred during PPD, which was detected using the 3,3 diaminobenzidine (DAB) in two contrast cassava genotypes, MNP Local A (29–57 µg g–1) and Sree Prakash (64–141 µg g–1). Accumulating the fluorescence hydroxycoumarin compounds emitted by the cassava tubers observed under an ultraviolet (UV) lamp showed significant variations at 0, 3, 6, 9, 12, and 15 days of storage. The accumulation of total phenolics, and flavonoids, carotenoids, and anthocyanin has a significantly role inand negatively correlated with PPD progression; however, the anthocyanin and flavonoids positively correlated with the PPD–anchored ROS accumulation. The major primary compound, Phthalic acid, di(2-–propylpentyl) ester, was identified in both the cassava tubers, Sree Prakash (57.21% and 35.21%), and MNP Local A (75.58% and 60.21%) at 0, and 72 h of PPD, respectively.in both the cassava tubers under PPD progression. The expression of PPD–associated genes, APX–2, APX–3, PAL, and AP was higher at 6–12 days of PPD, which signified the synthesis of ROS turnover and phenylpropanoid biosynthesis. A significant, strong, and positive correlation was established between the secondary metabolites and PPD signaling gene expression, which was inversely correlated with hydroxycoumarin and H2O2 accumulation. MNP Local A tubers exhibited longer storage life of 15 days with a low PPD score, higher metabolites synthesis, and gene expression. The PPD-–resistant lines may be used to augment cassava breeding strategies for large–scale commercial and industrial use.